2006
DOI: 10.1111/j.1744-9987.2006.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Purification for Critical Illness: Cytokines Adsorption Therapy

Abstract: Blood purification therapies have been clinically applied to treat cytokine-induced pathological effects. The effects of broad-spectrum adsorption using Lixelle (beta2-microglobulin adsorption column; Kaneka Corporation, Osaka, Japan) for the condition of hypercytokinemia in vitro, in an animal model and in humans with sepsis were investigated. We found that Lixelle could selectively adsorb not only beta2-microglobulin but also cytokines composed of glycoproteins in vitro. In addition, Lixelle beads could adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Furthermore, TNFα is related to ARDS/ALI and plays a role same as IL‐1β. However, we did not measure TNFα because it was previously reported that TNFα was not adsorbed in the column (22). We were not able to measure IL‐1α, a member of the IL‐1 family, because we did not have a measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNFα is related to ARDS/ALI and plays a role same as IL‐1β. However, we did not measure TNFα because it was previously reported that TNFα was not adsorbed in the column (22). We were not able to measure IL‐1α, a member of the IL‐1 family, because we did not have a measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new forms of AN69 (AN69 ST and AN69 Oxiris) do not anymore induce a bradykinin syndrome when in the presence of angiotensinconverting enzyme inhibitors. 55 They can still run with an hemoperfusion device. 18,47 Conclusions So far, after the failure of the major randomized studies on dose, attention is now drawn to new membranes that could better in wide spectrum and also could eliminate massive amounts of unbound mediators in great magnitude.…”
Section: Current Status and Recent Advances Regarding Blood-membrane mentioning
confidence: 99%
“…TNF, a 51 kD pro‐inflammatory cytokine, is removed at a slow rate within the device compared with smaller cytokines, putatively due to hindered diffusion of the large trimeric TNF molecule within the sorbent pores. Similar deficiencies in TNF capture have been reported using other cytokine‐targeted sorbent materials 26–29. Small sorbent pores are necessary to prevent essential large plasma proteins such as albumin from being removed by the device; hence, our goal was to develop strategies to accelerate TNF removal while maintaining an optimal pore size for whole blood filtration.…”
Section: Discussionmentioning
confidence: 69%
“…Similar deficiencies in TNF capture have been reported using other cytokine-targeted sorbent materials. [26][27][28][29] Small sorbent pores are necessary to prevent essential large plasma proteins such as albumin from being removed by the device; hence, our goal was to develop strategies to accelerate TNF removal while maintaining an optimal pore size for whole blood filtration. This work investigated the structural behavior of oligomeric TNF in vitro, and sought to quantify how specific perturbations of TNF quaternary structure would affect TNF capture within the hemoadsorption device.…”
Section: Discussionmentioning
confidence: 99%